Treating filtered final effluent from the Cape Flats Wastewater treatment plant with ozone and biologically activated carbon filtration to remove pathogens and organic micropollutants - Smuts, Francois (Department of Civil Engineering, 2022)
Final effluent is widely recognised as a risky water source for human consumption given the organic micropollutants and pathogens it can contain. Hence, multi-barrier treatment trains and advanced processes are required. However, these are costly and therefore it is necessary to investigate how their cost can be optimized. Plumlee et al. (2014) asserted that quantifying the cost of advanced treatment processes can help compare treatment alternatives and utilities' planning. The focus of the current study has been the cost optimisation of treatment processes in the treatment train of the Managed Aquifer Recharge (MAR) scheme of the Cape Flats Aquifer, one of the new bulk water schemes that originated out of the Cape Town drought peak during the period spanning between 2015–2017. It is an indirect potable reuse scheme that consists in injecting advanced treated final effluent from the Cape Flats MAR WRP into the Cape Flats Aquifer. Within the Cape Flats MAR WRP is the O3/BAC process, which is one of the advanced treatment processes at the facility. This process is essential given its ability to remove pathogens and organic micropollutants, i.e. it doubles as a disinfection step and an organic micropollutant removal step. However, the downside of the O3/BAC process is its costs, particularly its capital and operating costs given the many variables affecting the removal efficiencies, and hence, the costs. Among these variables are the treatment objectives, energy usage and liquid oxygen usage. The main factors impacting the removal efficiency are the water quality (O3 decay and instantaneous ozone demand [IOD]) and contact time. Therefore, the challenge is to carefully optimise the process without influencing the treatment objectives. In light of this, the main research question that the current study tries to answer is about the optimum cost of the O3/BAC filtration process for various treatment objectives to help produce safe drinking water in a treatment train. The aim of the current research is to study the interdependencies between the varying treatment objectives, the optimum operating conditions, and the efficiency of the O3/BAC process to inactivate pathogens and remove organic micropollutants. The optimisation focusses on the filtered secondary effluent of the Cape Flats Wastewater Treatment Works (WWTW) with the aim to produce safe drinking water. The research uses the O3 process assessment methods, i.e. the T10 method and CSTR methods, and the O3/TOC dose ratio as the main parameters to compare and relate the treatment objectives and the assessment methods with one another. The use of the O3/TOC dose ratio is motivated by the findings of Snyder et al. (2014), which stated that the O3/TOC dose ratio produces similar treatment results, particularly oxidation, even with high variations in water quality. Gamage et al. (2013) also asserted that the O3/TOC dose ratio relates the O3 dose required for disinfection and the O3 dose required for organic micropollutants oxidation. On one hand, the CT-value (product of residual O3 concentration and contact time) guarantees that the O3 process achieves its objectives concerning the removal of pathogens. On the other hand, the O3/TOC dose ratio together with each pollutants O3 and hydroxyl radical second-order reaction rates, kO3 and kOH, allow the quantification of the removal of organic micropollutants. Additionally, the current research uses capital and operation and maintenance (O&M) costing models, including process performance regression models, applied to various treatment objectives of the O3/BAC filtration process and to organic micropollutants found in the Cape Flats WWTW final effluent. The current study finds that the O3/BAC process of the Cape Flats MAR WRP can theoretically reduce more than 87% of the organic micropollutants in the Cape Flats WWTW final effluent, taking it from medium risk to low risk. The optimum contact time, in terms of cost for 2–4 Log virus inactivation by ozone and 1–3 Log giardia inactivation by ozone, is between 5–7 minutes as determined by the CSTR method, and it is 5 minutes as determined by the T10 method. The optimum contact time, in terms of cost for 1–3 log inactivation of cryptosporidium by ozone, is between 8–18 minutes for the CSTR method and between 6–13 minutes for the T10 method depending on the treatment objective and O3 transfer efficiency. No apparent correlations between international concept costing models and actual Southern African O3/BAC project costs were evident. The process assessment method, i.e. T10 or CSTR, affects the cost of the process and the performance objective that can be validated. Hence, the treatment of filtered final effluent by the O3/BAC process can be optimized for specific treatment objectives to produce safe drinking.